Handbook of research on techno-entrepreneurship : how technology and entrepreneurship are shaping the development of industries and companies - Therin, Francois (Cheltenham Edward Elgar Publishing Ltd., 2013)
Summary from British Library Catalogues: This up-to-date second volume of a high-quality Handbook examines the latest trends in techno-entrepreneurship. From family-business, to green entrepreneurship or effectuation, the major topics are covered with insightful recommendations for researchers and practitioners. With chapters focusing on China, India, South-East Asia and South America, the Handbook explores views on the new hot spots in techno-entrepreneurship development.
Introduction --
1. The Knowledge base of technology entrepreneurship / Ivan Zupic --
2. Technology entrepreneurship, innovation and iIntrapreneurship - managing entrepreneurial activities in technology-intensive environments / Alexander Brem and Jens Borchardt --
3. Technology in family business studies. a bibliometric analysis (1991 - 2012) / C. Dessi, M. Floris and A. Sanna --
4. Capitalization of science and technology knowledge: practices, trends and impacts on techno-entrepreneurship / Diane A. Isabelle --
5. Commercialization process of innovation in small high-technology firms - theoretical review / Jarkko Pellikka --
6. Technology entrepreneurship in china: what do chinese science and technology parks do for entrepreneurs? The exemplary case of jiangsu / Dominique Jolly and Fuquan Zhu --
7. What is e-entrepreneurship? Fundamentals of company founding in the net economy / Tobias Kollmann --
8. Venture capital financing of techno-entrepreneurial start-ups: drivers and barriers for investments in research-based spin-offs in the dutch medical life sciences industry / Joyce Houterman, Vincent Blok and Onno Omt --
9. Working as technology scout techno-intrapreneur / Magnus Hoppe --
10. The Role of academicians in technology entrepreneurship / Mohar Yusof, Mohammad Saeed Siddiq and Leilanie Mohd Nor --
11. Personal attributes of academic entrepreneurs / Hafizul Othman, Rosni Abdullah and Nasriah Zakaria --
12. Companies spun out of universities: different typologies for different performance patterns / Giuseppe Criaco, Christian Serarols-Tarres, Tommaso Minola and Apurav Yash Bhatiya --
13. The Role of the technology transfer office in promoting university-industry collaboration / Ciara Fitzgerald, Margaret Ledwith and Rory O'Shea --
14. Demand competition and entrepreneurial (de novo) entry in industries based on systemic technologies / Lalit Manral --
15. Nascent technology entrepreneurship supply chain emergence / Jennifer L. Woolley --
16. Frugal innovation and returnee-diaspora entrepreneurship / Preeta M. Banerjee and Ana Leirner --
17. Drivers of green strategy for enhancing sustainable techno-preneurship in emerging economies / Broto Rauth Bhardwaj and Kee-hung Lai --
18. The Path to sustainable technological entrepreneurship / Manjula S. Salimath and William Carter
Includes bibliographical references and index
Keywords: Management and auxiliary services; TECHNOLOGY; HIGH TECHNOLOGY; INDUSTRY; MANAGEMENT; TECHNOLOGICAL INNOVATIONS; ENTREPRENEURSHIP